Modul Socioecopreuner Cilik Sebagai Inovasi Edukasi untuk Pengembangan Pariwisata Lokal di Kabupaten Pohuwato - Abbas, Moh. Jenli; Samad, Pratiwi; Munir, Fairus Suryani (Indo-MathEdu Intellectuals Journal, 2025)
The tourism industry of Pohuwato Regency, Bajo Torosiaje village, Gorontalo Province, particularly in the aspects of social, environmental, and economic sustainability, as well as efforts to improve the quality of human resources as a differentiator from other programs. This research uses a Research and Development (R&D) approach, focusing on the business planning of socioecopreneurship that encompasses entrepreneurship and social activity materials with the instilling of socioecopreneur character values, tailored for elementary school students. The data collection technique uses questionnaires and the data analysis technique involves descriptive statistical analysis. The research results show that the ecopreneurship-based learning approach significantly increases students' entrepreneurial interest and environmental literacy. The interest score increased from 69 to 72, while the percentage of students with low interest decreased from 27% to 3%. A total of 80% of students expressed satisfaction with the implementation of this module. This indicates a stronger understanding of sustainability and students' readiness to become young ecopreneurs who care about the environment.